2023
DOI: 10.3390/catal13111410
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis on Pulsed Electrolysis: Electronic Effect, Double Layer Effect, and Mass Transport

Zhuowen Wang,
Yijun Liu,
Sibei Liu
et al.

Abstract: Pulsed electrolysis endowed merits of high current density, low energy consumption, and simple operation; thus, a booming in their publication numbers has been witnessed in recent years. In this review, we aim to summarize the state-of-the-art pulsed current/potential strategy to enhance electrochemical reactions, such as oxygen reduction reactions (ORR), CO2 reduction (CO2RR), CO reduction (COR), etc. It begins with historic analysis of pulsed electrolysis via a bibliometric method, aiming at providing a prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Pulsed electrolysis has been explored as a method to suppress the concentration polarization that occurs in the diffusion layer during electrocatalysis by promoting ion diffusion that periodically renews the electrode-electrolyte interface, 9,12,36,37 including during − NO 3 reduction. 7,[38][39][40] Guo et al found that pulsed electrolysis (10 s symmetric pulse) at a Ti cathode during − NO 3 reduction in a nonbuffered electrolyte showed an improvement in NH 3 selectivity but also an increase in H 2 production when compared to constant potential experiments under the same conditions, and had similar product selectivity to a 0.5 M phosphate buffer with a bulk pH of 10.5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed electrolysis has been explored as a method to suppress the concentration polarization that occurs in the diffusion layer during electrocatalysis by promoting ion diffusion that periodically renews the electrode-electrolyte interface, 9,12,36,37 including during − NO 3 reduction. 7,[38][39][40] Guo et al found that pulsed electrolysis (10 s symmetric pulse) at a Ti cathode during − NO 3 reduction in a nonbuffered electrolyte showed an improvement in NH 3 selectivity but also an increase in H 2 production when compared to constant potential experiments under the same conditions, and had similar product selectivity to a 0.5 M phosphate buffer with a bulk pH of 10.5.…”
mentioning
confidence: 99%
“…The pulse duration must be longer than the charge and discharge times of the double layer, otherwise the current will not reach the desired Faradaic current when pulsed on and it will not reach zero current when pulsed off. 9,37 Future work to decrease the measurement time for the ATR-SEIRAS technique will enable further exploration into the possibility of using pulsed electrolysis to maintain a desired interfacial pH. S15).…”
mentioning
confidence: 99%